1996
DOI: 10.1079/pns19960015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fatty acids and dietary lipids on cells of the immune system

Abstract: Effets des acides gras et des lipides de l'alimentation sur les cellules du systi2me immunitaire R E S U M ELa synthkse des acides gras de novo fournit de l'acide palmitique. Celui-ci peut Ctre allongC jusqu'h l'acide stCarique, un substrat de Pa Ay-dCsaturase, donnant ainsi de l'acide olkique (18:ln-9). Les animaux ne posskdent pas les enzymes A12-ou A15-dCsaturase qui produisent les acides linolCic (18:2n-6) et a-1inolCique (18:3n-3) respectivement; ces enzymes se trouvent dans des plantes qui contiennent do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
5

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 122 publications
(118 reference statements)
0
55
0
5
Order By: Relevance
“…Studies concerning eicosanoid synthesis by lymphocytes have proved controversial (see Goldyne, 1988). Many studies indicate that lymphocytes do not synthesize cyclooxygenase or lipoxygenase products (for references, see Goldyne, 1988;Calder, 1996b). Nevertheless, lymphocytes contain similar amounts of arachidonic acid in their membrane phospholipids to macrophages and mitogen-stimulated lymphocytes release arachidonic acid extracellularly.…”
Section: 59mentioning
confidence: 99%
“…Studies concerning eicosanoid synthesis by lymphocytes have proved controversial (see Goldyne, 1988). Many studies indicate that lymphocytes do not synthesize cyclooxygenase or lipoxygenase products (for references, see Goldyne, 1988;Calder, 1996b). Nevertheless, lymphocytes contain similar amounts of arachidonic acid in their membrane phospholipids to macrophages and mitogen-stimulated lymphocytes release arachidonic acid extracellularly.…”
Section: 59mentioning
confidence: 99%
“…On the other hand, an excessive amount of n-6 PUFA, in diet poor in n-3 PUFA, can contribute to PGE 2 , TXA2 and LTB 4 overproduction -potent inflammatory mediators. Eicosanoids produced from EPA (n-3 PUFA) are, in general, less active in inflammatory process than derived AA eicosanoids (Calder 1996, Kikuchi et al 1998. The inflammatory response is designed to remove the inciting stimulus and resolve tissue damage.…”
Section: Inflammatory Bowel Disease and Dietary Fatty Acidsmentioning
confidence: 99%
“…Similar results have been observed in regard to H 2 O 2 production. It has previously been demonstrated that peritoneal macrophages from mice that were fed on a diet supplemented with fish oil over a period of eight weeks produced more H 2 O 2 in response to stimulation by a phorbol ester than peritoneal macrophages from mice fed on a diet supplemented with coconut oil (Calder 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Because n-3 PUFA-rich diets can affect the production of these eicosanoids, it is expected that these fatty acids can directly affect cytokine production (Calder 1996(Calder , 2002.…”
Section: Discussionmentioning
confidence: 99%